Systematics of spiny-backed treefrogs (Hylidae: Osteocephalus): An Amazonian puzzle - Jungfer, Karl-Heinz; Faivovich, Julián; Padial, José M.; Castroviejo-Fisher, Santiago; Lyra, Mariana M. [UNESP]; V. M. Berneck, Bianca [UNESP]; Iglesias, Patricia P.; Kok, Philippe J. R.; Macculloch, Ross D.; Rodrigues, Miguel T.; Verdade, Vanessa K.; Torres Gastello, Claudia P.; et al. (Wiley, 2013)
Spiny-backed tree frogs of the genus Osteocephalus are conspicuous components of the tropical wet forests of the Amazon and the Guiana Shield. Here, we revise the phylogenetic relationships of Osteocephalus and its sister group Tepuihyla, using up to 6134 bp of DNA sequences of nine mitochondrial and one nuclear gene for 338 specimens from eight countries and 218 localities, representing 89% of the 28 currently recognized nominal species. Our phylogenetic analyses reveal (i) the paraphyly of Osteocephalus with respect to Tepuihyla, (ii) the placement of 'Hyla' warreni as sister to Tepuihyla, (iii) the non-monophyly of several currently recognized species within Osteocephalus and (iv) the presence of low (<1%) and overlapping genetic distances among phenotypically well-characterized nominal species (e.g. O. taurinus and O. oophagus) for the 16S gene fragment used in amphibian DNA barcoding. We propose a new taxonomy, securing the monophyly of Osteocephalus and Tepuihyla by rearranging and redefining the content of both genera and also erect a new genus for the sister group of Osteocephalus. The colouration of newly metamorphosed individuals is proposed as a morphological synapomorphy for Osteocephalus. We recognize and define five monophyletic species groups within Osteocephalus, synonymize three species of Osteocephalus (O. germani, O. phasmatus and O. vilmae) and three species of Tepuihyla (T. celsae, T. galani and T. talbergae) and reallocate three species (Hyla helenae to Osteocephalus, O. exophthalmus to Tepuihyla and O. pearsoni to Dryaderces gen. n.). Furthermore, we flag nine putative new species (an increase to 138% of the current diversity). We conclude that species numbers are largely underestimated, with most hidden diversity centred on widespread and polymorphic nominal species. The evolutionary origin of breeding strategies within Osteocephalus is discussed in the light of this new phylogenetic hypothesis, and a novel type of amplexus (gular amplexus) is described. © 2013 The Norwegian Academy of Science and Letters.
Keywords: Amphibia; Anura; Hyla; Hylidae; Osteocephalus; Osteocephalus oophagus; Osteocephalus taurinus; Tepuihyla